2006
DOI: 10.1021/es061771r
|View full text |Cite
|
Sign up to set email alerts
|

Levels, Tissue Distribution, and Age-Related Accumulation of Synthetic Musk Fragrances in Chinese Sturgeon (Acipenser sinensis):  Comparison to Organochlorines

Abstract: Chinese sturgeon (Acipenser sinensis) was listed as a Grade I protected animal in China in 1989, and the observed intersexual phenomenon and sex ratio deviation have suggested that chemicals have posed a risk as environment pollutants. This study analyzed seven musk fragrances in liver, muscle, heart, gonad, stomach, intestines, adipose, gill, pancreas, kidney, gallbladder, and roe from 13 female Chinese sturgeons, and the toxicokinetic behavior of musks were studied and compared with some organochlorines. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 38 publications
3
49
2
Order By: Relevance
“…The results indicated the widespread contamination of synthetic musk fragrances in the marine environment in China. The existence of synthetic musk fragrances in fish tissues of Chinese sturgeon has been verified by Hu et al [26]. Thus far, no study exists on the occurrence of synthetic musk fragrances in humans, such as in blood, human tissues, and mother's milk, in China.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The results indicated the widespread contamination of synthetic musk fragrances in the marine environment in China. The existence of synthetic musk fragrances in fish tissues of Chinese sturgeon has been verified by Hu et al [26]. Thus far, no study exists on the occurrence of synthetic musk fragrances in humans, such as in blood, human tissues, and mother's milk, in China.…”
Section: Introductionmentioning
confidence: 93%
“…In the present study, d 10 -fluoranthene was used as a surrogate standard, which was also adopted by other researchers because the compound showed similar physicochemical properties with musks such as logarithm octanol-water partition coefficient (5.22 for d 10 -fluoranthene [6] and 4-6 for musks [26,27]). To verify the suitability of d 10 -fluoranthene as a surrogate standard for all of synthetic musk compounds during the above pretreatment, the recovery experiments (1.5 mg/L, n ¼ 6) were conducted.…”
Section: Instrumental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…9, 5.7, 4.3, and 4.9, respectively], SM are expected to bio-accumulate in aquatic biota. Previous studies have shown widespread occurrence of SM in aquatic biota including fish, crustaceans and mussels (Kannan et al 2005;Wan et al 2007), as well as top order predators such as sharks, seals, and finless porpoises (Nakata 2005). SM have also been detected in human adipose tissues (Müller et al 1996), blood plasma (Hutter et al 2005), and human breast milk (Duedahl-Olesen et al 2005;Reiner et al 2007;Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Nakata et al, 2005a). Concentrations of OCPs in different tissues of Chinese Sturgeon were investigated (Wan et al, 2007). HCB was detected in all the samples, and HCB concentrations (224-2600 ng/g lipid wt.)…”
Section: Fish and Shellfishmentioning
confidence: 99%